From Tap to Tablet to Table: How the Water–Food–Drug Exposome Drives Early-Onset Noncommunicable Diseases - SANGWA, Sixbert; MUTABAZI, Placide (My University, 2025)
Background: Non-communicable diseases (NCDs) already claim more than 40 million lives annually and are now emerging in adolescence and early adulthood, a trend not fully explained by ageing or lifestyle alone. Objectives: This study evaluated whether chemically treated water, industrialised food systems, and pharmaco-centric healthcare converge into a single exposome that accelerates early-onset NCDs and neurocognitive decline while tacitly advancing long-standing depopulation ideologies nurtured by clandestine policy networks. Methods: Evidence from 1990–2025 toxicological and epidemiological meta-analyses, WHO and Global Burden of Disease datasets, and declassified governmental and corporate archives was triangulated. A text-mining pipeline guided study selection; random-effects models generated pooled risk estimates; causal-loop diagramming mapped feedbacks among exposure, regulation, and disease. Results: High-quartile trihalomethanes in drinking water, intensive pesticide and ultra-processed-food intake, and polypharmacy of five or more drugs were each associated with 20–58 percent increases in youth-onset metabolic syndrome, cognitive impairment, and site-specific cancers. Composite exposure indices explained 43 percent of the variance in 25–49-year DALYs after GDP adjustment. Historical review uncovered recurring eugenic and technocratic incentives, ranging from Project Coast’s covert anti-fertility experiments to suppressed PFAS toxicity dossiers, delineating a century-long blueprint to modulate fertility and morbidity curves. Conclusions: The water–food–drug exposome functions as a synergistic low-dose toxic matrix that is shifting the global NCD burden leftward and inadvertently furthering depopulation-oriented objectives. Effective mitigation requires mixture-aware regulation, non-chlorine disinfection, agro-ecological farming, and prescription policies that limit metabolic externalities. Integrating exposomic science with historical-ethical analysis can realign public-health policy with the integrity of created biological design.